Costing adult attention deficit hyperactivity disorder : impact on the individual and society - Daley, David,..[et al.] (Oxford University Press, 2015)
This book estimates the private and social costs of ADHD. It studies the costs related to individuals with ADHD who have not been diagnosed and who have not received treatment. in this respect, it makes a unique contribution to scientific knowledge by investigating the cost of untreated ADHD. It also investigates the extent to which individuals with undiagnosed ADHD in childhood fare differently compared to otherwise similar individuals without ADHD. A long list of important parameters in an individual's life, e.g. educational attainment, occupational status, income, family situation, criminal record, and health are eexamined The results provide not just cost estimates of ADHD but also a point of reference that will be highly relevant for the evaluation of any future treatment for ADHD.--